Trade union renewal and 'organizing from below' in Germany: Institutional constraints, strategic dilemmas and organizational tensions. (March 2019) - Nicklich, Manuel; Helfen, Markus
Organizing is widely discussed as a remedy for continued union decline. Originating in the liberal market industrial relations systems of the Anglo-Saxon world, the 'organizing' strategy is increasingly discussed in countries like Germany, traditionally known for consensual industrial relations and multi-employer collective bargaining. To study whether and how 'organizing' is translated in union organizations operating in a different institutional context, we study the link between organizational transformation and institutions in IG Metall in Germany, which was been influenced by the American Service Employees International Union (SEIU). We find a German variety of organizing rather than a mere copying of 'best practice': the union's approach is based on institutional and organizational structures as a resource and constraint.